Internet of Things and the challenges for cross-border network slicing in 5G-based smart networks - Günter Knieps (International Telecommunications Society (ITS), 2022)
The transition towards 5G-based smart network industries is concomitant with a fundamental change of the traditional physical infrastructures driven by digitalization which pervades all decision-relevant components of the infrastructure value chains. The goal of this paper is to develop a network economic foundation for 5G based network slicing based on a generaliza-tion of the concept of virtual networks combining a required sequence of virtual networks in order to fulfill the necessities of smart network industries. Whereas interoperability and inter-connection between different virtual networks are not standardized significant standardization efforts via network slicing can be observed in particular from the perspective of end-to-end QoS guarantees. 5G-based big data use cases with cross-border challenges for network slic-ing, and the subsequent interoperability of virtual networks, enable tremendous potential for innovation in smart physical infrastructures. The 5G-based European Future Railway Mobile Communication System (FRMCS) and cross-border oriented, 5G-based connected, coopera-tive, and automated mobility applications (CCAM) are investigated with a large and open set of heterogeneous use cases begging for cross-border standardization of QoS-differentiated network slices.
Keywords: 330